Aplikasi Sistem Informasi Geografis untuk Identifikasi Potensi dan Kerentanan Longsor di Kabupaten Bondowoso Provinsi Jawa Timur - RAHMAN, AHMADI FAUZAN NUR; TRIGUNASIH, NI MADE; ARTHAGAMA, I DEWA MADE; SAIFULLOH, MOH (Agrotrop : Journal on Agriculture Science; Vol 13 No 2 (2023), 2023)
Application of Geographic Information System for Identification of Landslide Potential and Susceptibility in Bondowoso Regency . The study was to determine the potential and susceptibility of landslides, as well as to determine the distribution of landslide points in Bondowoso Regency. This research uses a survey and scoring method which refers to PSBA UGM (2001) and BNPB (2012). The parameters used in this study were five, namely soil movement, presipitation, soil type, slope, and land use. The landslide susceptibility level is obtained by overlapping the landslide potential map and the vital land use map. The class of landslide potential in Bondowoso Regency is categorized into areas with no potential to high landslide potential. The class with no potential spread in the lowlands is 27,906.57 ha or 18.27%, the low potential class is 60,391.34 ha or 39.53%, the medium potential class is 43,803.54 ha or 28.67% and the high potential class covering an area of 20,685.32 ha or 13.54% of the total area of Bondowoso Regency. Areas with high landslide susceptibility are Grujugan, Klabang, Maesan, Pakem, and Sempol sub-districts with 50 landslide points found in the sub-district.